2020
DOI: 10.1172/jci.insight.132796
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection by nanomaterials formulated with CHIR99021 and FGF1

Abstract: NPs encapsulated with CHIR + FGF1 exerted substantial myocardial protective effects and represents a potentially novel strategy for improving postischemic myocardial protection. Results Identification of chemicals that promote cell cycle activity of human induced pluripotent stem cell-derived cardiomyocytes. Using the BrdU incorporation assay, we screened several chemicals for their capacity to enhance the cell cycle activity of cultured human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 52 publications
(57 reference statements)
0
26
0
Order By: Relevance
“…High biocompatibility and low cytotoxicity are attributed to the degradation byproducts—lactate and glycolate—which can easily be incorporated into cellular metabolic pathways ( Figure 1 ) ( Chereddy et al, 2018 ). Due to these highly desirable properties, PLGA has been widely studied as both a therapeutic and diagnostic agent in the cardiac field as well ( Oduk et al, 2018 ; Zhang et al, 2019 ; Fan et al, 2020a ; Fan et al, 2020b ). With improvements in processing and production techniques, PLGA has also enjoyed a lot of attention due to the relative ease with which comparatively large batches of nano-medicines can be produced via emulsion polymerization.…”
Section: Types Of Scaffold In Nano-medicinementioning
confidence: 99%
See 1 more Smart Citation
“…High biocompatibility and low cytotoxicity are attributed to the degradation byproducts—lactate and glycolate—which can easily be incorporated into cellular metabolic pathways ( Figure 1 ) ( Chereddy et al, 2018 ). Due to these highly desirable properties, PLGA has been widely studied as both a therapeutic and diagnostic agent in the cardiac field as well ( Oduk et al, 2018 ; Zhang et al, 2019 ; Fan et al, 2020a ; Fan et al, 2020b ). With improvements in processing and production techniques, PLGA has also enjoyed a lot of attention due to the relative ease with which comparatively large batches of nano-medicines can be produced via emulsion polymerization.…”
Section: Types Of Scaffold In Nano-medicinementioning
confidence: 99%
“…Recent studies showing the synergistic effects of using a combination of extended delivery of CHIR99021 (a Wnt1 agonist/GSK-3β antagonist) and fibroblast growth factor 1 (FGF1) to protect ischemia-threatened cardiomyocytes from apoptosis, while accelerating angiogenesis through the promotion of endothelial and vascular SMC proliferation, and consequently enhance myocardial protection have been published ( Fan et al, 2020a ; Fan et al, 2020b ). These studies found that PLGA NPs loaded with CHIR99021 or FGF1 allowed for effective delayed release for up to 4 weeks.…”
Section: Types Of Loads Deliveredmentioning
confidence: 99%
“…Fan et al identified acidic fibroblast growth factor (FGF-1) and CHIR99021 as synergistic enhancers of cardiomyocyte cell cycle activity [ 62 ]. CHIR99021 is an aminopyrimidine derivative that functions as a Wnt signaling activator, which has also been shown to be able to reprogram fibroblasts to a cardiomyocyte phenotype [ 63 ].…”
Section: Cell-free Cardiac Regeneration Therapiesmentioning
confidence: 99%
“…In their study, both molecules were loaded onto PLGA nanoparticles and injected intramyocardially 15 min after reperfusion of AMI in a pig model ( n = 12). This resulted in significantly reduced scarring as well as increased LVEF and decreased left ventricular end-diastolic volume (LVEDV) compared to control animals after 28 days of follow-up [ 62 ].…”
Section: Cell-free Cardiac Regeneration Therapiesmentioning
confidence: 99%
“…As the functionality of cardiomyocytes proliferation is limited in an adult mammal heart, promotion of angiogenesis remains the most crucial strategy in salvaging myocytes at the infarcted border zone. Thus, discovering practical or appropriate clinical interventions, sparing less severely damaged myocytes at border zones, could effectively reduce infarct size and save lives ( Fan et al, 2020a ). Mesenchymal stromal cells (MSCs) represent a promising tool for cell therapy, particularly for heart-related diseases.…”
Section: Introductionmentioning
confidence: 99%